Investigation on ultrasonication mediated biosurfactant disintegration method in sludge flocs for enhancing hydrolytic enzymes activity and polyhydroxyalkanoates. Issue 27 (6th December 2019) - Sethupathy, A.; Sivashanmugam, P.
ABSTRACT: In this study, a novel biosurfactant potential bacterial strain Pseudomonas pachastrellae RW43 was isolated from pulp and paper sludge and the biosurfactant namely rhamnolipid produced by Pseudomonas pachastrellae RW43 was investigated by varying pH and incubation time in batch liquid fermentation process. The maximal yield of rhamnolipid was found to be 12.1 g/L at an optimized condition of pH 7 and incubation time of 168 h. NMR analysis was performed for identification of molecular structure of produced rhamnolipid and its results concluded that the product was identified as di rhamnolipid. Then, statistically the global optimum conditions for hydrolytic enzymes extraction parameters (sonication power (100 W), extraction time (15 min) and rhamnolipid dosage (2% v/v)) were established. At 30, 456 kJ/kg TS specific energy, ultrasonication with rhamnolipid disintegration method extracted maximal consortium activity of hydrolytic enzymes from mixed sludge (municipal and pulp & paper sludge) and the maximum observed were found to be 42.22, 51.75, 34.26, 24.21, 11.35 Units/g VSS respectively for protease, α -amylase, cellulase, lipase and α -glucosidase. Polyhydroxyalkanoates was recovered from enzymes extracted sludge using various solvents namely chloroform, sodium hypochlorite with chloroform and sodium lauryl sulfate with sodium hypochlorite. The maximum recovery was found to be 74 g/kg using sodium hypochlorite and chloroform extraction solvents. GRAPHICAL ABSTRACT: